2012
DOI: 10.3168/jds.2012-5390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microbial survival post-incidence on fresh Mozzarella cheese

Abstract: Commercial fresh Mozzarella cheese is made by direct acidification and is stored dry or in water without salt addition. The cheese has a shelf life of 6 wk, but usually develops an off-flavor and loses textural integrity by 4 wk, potentially due to the lack of salt and high moisture that allow the outgrowth of undesirable bacteria. To understand how microbial incidence affects cheese quality and how incident pathogen-related bacteria are limited by salt level during refrigerated storage, we made fresh Mozzarel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…At day 28, treatment with CE showed a decrease in the number of coliform colonies (p < 0.05), compared with CR cheese. Similar results have been reported in related cheeses during ripening [11,18,20]. This behavior is caused by the development of starter cultures, as they at pH 4 and 5 in dairy products inhibit the common and pathogenic flora, achieving lengthen the shelf life of product.…”
Section: Total Coliforms Countsupporting
confidence: 83%
See 1 more Smart Citation
“…At day 28, treatment with CE showed a decrease in the number of coliform colonies (p < 0.05), compared with CR cheese. Similar results have been reported in related cheeses during ripening [11,18,20]. This behavior is caused by the development of starter cultures, as they at pH 4 and 5 in dairy products inhibit the common and pathogenic flora, achieving lengthen the shelf life of product.…”
Section: Total Coliforms Countsupporting
confidence: 83%
“…Several authors have reported the use of plant's enzymes (cardosins from Cynaras) in different handmade cheeses and showed that the sensory characteristics of those cheeses are similar or better than cheeses manufactured with commercial rennet [8][9][10]. Similar cheeses to asadero cheese have a shelf life of 6 wk, but usually develops an off-flavor and loses textural integrity by 4 wk, potentially due to the lack of salt and high moisture that allow the outgrowth of undesirable bacteria [11].…”
Section: Introductionmentioning
confidence: 99%
“…Coliform counts were slightly higher than those found in a previous study on raw-milk Oaxaca cheese, whereas counts of E. coli were similar (Caro et al, 2013). Coliforms and E. coli are related to fecal contamination and are used as an index of hygiene in cheese (Ganesan et al, 2012). Moreover, coliforms are considered one of the most important spoilage bacteria in mozzarella cheese (De Angelis et al, 2008).…”
Section: Changes In Microbial Populations Of Cheeses During Storagementioning
confidence: 67%
“…It has a mild flavor (Rankin et al, 2006) that tastes like lightly salted, fresh milk (Ganesan et al, 2012). Just as Swiss cheese is known universally for its holes, string cheese is known for its stringing properties, as shown in Figure 2.…”
Section: Properties Of String Cheesementioning
confidence: 99%
“…Because string cheese has a high moisture content (> 45 but ≤ 52 percent) and low salt content (1.6 percent), it has greater potential to spoil due to yeast, mold, and coliform growth (Guinee, 2004). Proper pasteurization, refrigeration and low pH of less than 5.4 are the only deterrents to the growth of unwanted microorganisms during storage (Ganesan et al, 2012).…”
Section: Expected Shelf Life Of String Cheesementioning
confidence: 99%